Детское время: [стихи] / Михаил Яснов ; художник Ю. Богатова - Яснов Михаил Давидович (ДЕТГИЗ-Лицей, 2007)
Экземпляры: аб. (2010) / Инвентарный номер: 53227 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Я 82 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5